From Tweets to Thrills: The Evolution of Digital Storytelling on YouTube through Nessie Judge's Horror Narratives - Diego, Diego; Lestari , Yayuk; Sarmiati, Sarmiati (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
This research investigates the widespread and even impact phenomenon generated by the audience's enthusiasm for YouTube content presented by Nessie Judge. Nessie Judge's unique narrative style has successfully sparked strong enthusiasm among YouTube subscribers, who eagerly await each episode of her content with excitement. This study holds significant significance as it examines Nessie's storytelling ability, often supported by compelling evidence and presented from a deep perspective. The horror genre in the story "Cerita KKN Desa Penari" ("The Story of Village Penari's Internship Program") is effectively conveyed through the use of background sound that creates tension, providing an intense experience for listeners. This phenomenon is not merely entertainment; it also encourages viewers to actively participate in the story interpretation process. Through the application of the six Critical Media Literacy (CML) concepts in analyzing media content, this research emphasizes the importance of critical media literacy as a tool to navigate the complex world of information. Critical media literacy offers profound insights and the ability to see beyond the presented message, which becomes increasingly crucial in an era deeply connected to media. This research encourages a deeper understanding that goes beyond the surface meanings of media messages. Through critical analysis, this study provides the potential for audiences to become more critical in understanding and interacting with media. This research provides profound insights into the impact of media content, particularly from Nessie Judge. However, factors influencing the audience's level of critical understanding of this content remain. The research underscores the importance of critical media literacy in facing the evolving media era, enabling audiences to interpret media messages in a more informed and critical manner. The contribution of this study has a significant impact on the development of knowledge, especially in the cultivation of critical understanding of media content and its role in the evolution of the modern media environment.